Novel S2 subunit-specific antibody with broad neutralizing activity against SARS-CoV-2 variants of concern - Heo, Chang-Kyu; Lim, Won-Hee; Yang, Jihyun; Son, Sumin; Kim, Sang Jick; Kim, Doo-Jin; Poo, Haryoung; Cho, Eun-Wie (Frontiers in Immunology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease 2019 , had a major impact on both the global health and economy. Numerous virus-neutralizing antibodies were developed against the S1 subunit of SARS-CoV-2 spike (S) protein to block viral binding to host cells and were authorized for control of the COVID-19 pandemic. However, frequent mutations in the S1 subunit of SARS-CoV-2 enabled the emergence of immune evasive variants. To address these challenges, broadly neutralizing antibodies targeting the relatively conserved S2 subunit, and its epitopes have been investigated as antibody therapeutics and universal vaccines. Herein, we present a novel S2-specific antibody, 4A5, isolated from BALB/c mice immunized with inactivated SARS-CoV-2. 4A5 exhibited specific affinity to SARS-CoV-2 S2 subunits compared with those of other β-CoVs. 4A5 bound to epitope segment F1109-V1133 between the heptad-repeat1 (HR1) and the stem-helix (SH) region. The 4A5 epitope is highly conserved in SARS-CoV-2 variants, with a significant conformational feature in both pre-and postfusion S proteins. Notably, 4A5 exhibited broad neutralizing activity against variants and triggered Fc-enhanced antibody-dependent cellular phagocytosis. These findings offer a promising avenue for novel antibody therapeutics and insights for next-generation vaccine design.